Decision Support System for Tourist Destination Selection in Buleleng Using the Analytical Hierarchy Process (AHP) - Pradhana, Anak Agung Surya; Kotama, I Nyoman Darma (Jurnal Sistem Informasi dan Komputer Terapan Indonesia (JSIKTI), 2023)
Tourism is a key driver of regional economic development and cultural sustainability, particularly in destinations with diverse natural and cultural assets such as Buleleng, Bali. Yet, selecting the most suitable tourist location is often difficult because it involves various decision factors, including accessibility, attractiveness, available facilities, safety, cost, cleanliness, popularity, and visitor density, which can lead to decisions based on personal bias rather than objective evaluation. To address this challenge, this study develops a Decision Support System (DSS) using the Analytical Hierarchy Process (AHP) to systematically assess and rank tourist destinations in Buleleng based on eight priority criteria. The proposed approach provides a structured weighting mechanism and ensures logical consistency in comparisons, indicated by a Consistency Ratio (CR) of 0.000. The analysis results reveal that Pura Ulun Danu Beratan is the most recommended destination, followed by Lovina Beach and Sekumpul Waterfall, supported by their strong appeal and adequate supporting infrastructure. Future development of this system may involve incorporating real-time visitor data, sentiment analysis from online travel reviews, and GIS-based visualization, as well as deployment in web or mobile platforms to increase usability for travelers and local tourism planners.